Adolescent Barriers to Understanding Cancer Information:A Qualitative Study - Dina Rasmita; Dewi Elizadiani Suza; Dwi Karina Ariadni (Talenta Publisher, 2026)
Cancer-related information is widely accessible to adolescents through schools, families, social media, and their surrounding environment. However, adequate understanding has not necessarily been produced by increased access to information. In this study, adolescents' experiences of the barriers that are encountered in the accessing and understanding of cancer-related information were aimed to be explored. A qualitative study with a descriptive phenomenological approach was conducted. Eighteen Grade XII students from SMK Negeri 14 Medan were purposively selected and were participated in semi-structured interviews. The data were analysed manually using Colaizzi's phenomenological method. Three main themes were identified by the analysis: (1) difficulty in the understanding of complex and diverse cancer information; (2) difficulty in the filtering and prioritising of large volumes of cancer information; and (3) difficulty in the coping with uncertainty before an adequate understanding of cancer was developed. These barriers were associated with fragmented and limited information, unfamiliar medical terminology, communication that was not tailored to adolescents' level of understanding, the broad scope of cancer-related topics, challenges in the prioritising of information, confusion in the distinguishing between symptoms, prevention, and treatment, and the perception of cancer as an inevitable death sentence. It is suggested by the findings that cancer information for adolescents should be communicated using clear, age-appropriate language, be presented progressively, be tailored to their lived experiences, be delivered by trusted sources, and be designed with consideration for adolescents' psychological needs. Valuable insights for the development of school-based cancer education programmes and adolescent-centred nursing interventions are provided by these findings. Keywords: Cancer, Health literacy, Health information, Teenagers